Ozone generator
By employing a high-frequency power source and specific metal depositions on quartz pipes, the challenges of inefficient plating and high costs in ozone generator technology are addressed, resulting in effective low-concentration ozone generation for improved indoor air quality.
Patent Information
- Application Number
- JP2023178972
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-17
- Publication Date
- 2025-04-30
- Estimated Expiration
- 2043-10-17
AI Technical Summary
Conventional methods for plating metal ions on quartz pipes for ozone generators are inefficient, as they require expensive reducing agents and high-temperature processes, making it difficult to achieve uniform coating and high electrical conductivity.
The use of a high-frequency power source to supply current to a quartz pipe discharge tube, combined with the deposition of metals like W or Mo on the outer surface and Ti or Cr on the inner surface, along with a melt-baking process using boric acid and copper chloride, to enhance electrical conductivity and ozone generation.
This approach allows for the generation of low-concentration ozone effectively, improving indoor air quality and health environment management, while reducing costs and simplifying the plating process.
Smart Images

Figure 2025068883000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to Ozone Generator This is regarding. [Background technology]
[0002] As a method of attaching metal ions to an ozone generating discharge tube to cause continuous lightning, there is a method of plating using the AIP method (a technology that evaporates and ionizes a target metal by arc discharge in a vacuum, and coats a thin film on the base material to be treated) and a method of fusing metal ions to a quartz pipe using a baking method with enamel flux. Conventional technology does not attach metal ions to quartz pipes 100%. Air does not conduct electricity very well. Ozone is generally produced in cumulonimbus clouds. Lightning in the general atmosphere discharges at tens of thousands of volts (several million volts to tens of millions of volts) in a room and reaches the ground. By doing the same thing inside a quartz glass tube, ozone O3 is generated.
[0003] If there are three trees, one 20m tall, one 10m tall, and one 5m tall, the lightning will strike the 20m tree first. Unless this unevenness is created continuously within a short tube with an outer diameter of 15 mm, inner diameter of 13 mm, and length of 50 mm, a very high frequency power source would be required to generate a corona discharge in the air of an insulator. That being said, etching quartz (SiO2) is extremely difficult, and even immersing it in HF (fluorine) for 30 minutes makes it impossible to achieve a thickness on the order of μm. Experiments with aqua regia (nitric acid-1) (hydrochloric acid-3) did not produce the unevenness the inventors had envisioned. Experiments with aqua regia + chromic acid, aqua regia + fluoric acid, aqua regia + ferric acid, etc. also showed that it was impossible to achieve even 1 / 100 of the unevenness, and this was the limit. (Etching was necessary to create an anchor effect for the metal ions to adhere.)
[0004] The unevenness can be created by etching the quartz pipe with glass beads, so the baking flux (a kind of enamel) adhered 100%. After CuBF4 coating, baking was 100% successful even at 800℃ with CuBF4+H2BO3, but although a 45% solution of copper tetrafluoroborate (Cu+BF4)2 adhered 100% to the unevenness, it did not bake by itself. Baking was not possible unless it was combined with the (CH3)2N-CN(CH3)2 compound.
[0005] The inventor developed a glass plating method in Patent No. 6111385, and it seemed impossible to use ordinary technology. First, expensive palladium chloride (PdC 12 ), (TRC 12 ), (PtC 12 ) was not used. This is because it is possible to create surface and inner unevenness in units of several μm by glass bead etching. The reason for not using a reducing agent is that it is different from plating, which is called baking. In the world of enamel at 650 to 800 degrees Celsius, Ni ions are the limit for increasing electrical conductivity. The need to ensure that copper ions are added with CuCl2, Cu(BF4)2, and CuCO3 is necessary to generate coastal discharge at a low voltage. It started with a combination of ordinary silver solder flux, KHF2, KBF4, H2BO3, Na2B4O4, KF, and NaF, but simply put, although soldering and enamel have similar temperatures and fluxes, the more they are mixed the worse the adhesion becomes. SiO2 was not receptive to fluoride and chloride fluxes.
[0006] It was discovered that only SiO2+H3BO3 is accepted. H3BO3 acts as a flux to protect against oxidation up to 180-800℃. Therefore, H+O decomposes and evaporates, and only the remaining B becomes a compound glass of SiO2+B. Only CuCl2 and Cu(BF4)2 showed copper color. The inventors could not stay away from plating, and even with expensive PdCl2, plating on SiO2 was impossible with normal chemical plating. In a high-temperature furnace, oxygen does not enter the SUS304 container up to a maximum of 800°C, and the SUS304 container consumes O2 through high-temperature oxidation, leaving behind (B). B has a melting point of 2076°C and a boiling point of 4000°C, and cannot react with itself at 600-800°C, but the Kirkendall effect creates glass of SiO2+B. It was discovered that Cu ions, a metal ion, adhere to the material at this time.
[0007] 100% borosilicate glass has a thermal expansion coefficient of 3×10 -6 It is resistant to thermal shock because it is 1 / 3 the thickness of normal glass at 1 / K. It has the advantage of not breaking even if it is repeatedly cooled and heated, and I think that plating is possible because a very small amount of B is mixed into the 100% quartz glass, but this is to increase the discharge rate, and I think that the surface thickness is about 0.5μm on the outer diameter 15mm x inner diameter 13mm x length 50mm. Baking at 600~800℃ can be called enamel. Therefore, the following describes techniques that have been introduced in conventional patent documents.
[0008] The device in Patent Document 1 is a high-output ozone generator made by a major Japanese manufacturer. This device is entirely water-cooled. For tap water sterilization, pure oxygen is used instead of air to generate a large amount of ozone in an instant, and for injection sterilization, it is used in food factories and other places for up to 1000 people. 9 m 3 It sterilizes a large building at night. It sterilizes at 0.1-0.5ppm, which is the limit of human body, and 1ppm-5ppm for cockroaches and rats. In this invention, even a large hospital room is 85m3 and is air-cooled, so it is designed to be within 0.01-0.03ppm, and is entirely air-cooled. (The basic formula is building volume ÷ 2.14 = xppm.)
[0009] The device of Patent Document 2 makes it possible to simultaneously water-cool and dielectrically cool the high-voltage electrode side in order to improve cooling of the discharge gap of the ozone generating electrode, thereby suppressing heat generation. This invention is an air-cooled system.
[0010] The ozone generator in Patent Document 3 is a small ozone generator that uses corona discharge with a maximum of about 1000g / h and produces 5ppm or less by covering the inside and outside of a quartz pipe with an insulator made of electrically conductive air. Ionized metal It is an air-cooled ozone generator with a positive anode, which is plated with copper and wrapped with 800 to 1000 mesh copper wire mesh. For ultra-large ozone generators, the output is 10,000 to 50,000 PPM / h, and the entire device must be water-cooled. The present invention is a device that is within a max of 5ppm (always taking into account the 16-hour half-life).
[0011] The device in Patent Document 4 is a water-cooled type that generates ozone in the discharge gap. For this reason, the retainer is a block type that allows the ozone generating blocks to be stacked, but the inlet and outlet for the coolant (water) must be connected to holes inside the block retainer, and it is difficult to seal the holes for the ozone gas that passes through. In contrast to the water-cooled type, the present invention uses hole cooling.
[0012] The device in Patent Document 5 is a large-scale device in which ozone generators are modularized and stacked in multiple stages. Each module is a large-scale water-cooled device in which each module is cooled by a water channel. For this reason, it is necessary to take measures against water leakage at the connection parts, and to assemble and insulate the equipment, which is very laborious.
[0013] The ozone generator of Patent Document 6 is a type in which high voltage electrodes are passed from (+) to (-) on a ceramic plate, the passage for using cooling water is separated from the ozone gas passage, and the holder is made of ceramic and glass derivatives. In comparison, the ceramic generator of the present invention is very simple, and by putting metal ions (Cr+W) on the outside and Cu+P on the inside to perform coastal continuous corona discharge, it is small but ultra-compact, generating a maximum of 1000g / h of ozone. (It was discovered that 0.01ppm / h to 0.05ppm / h is an amount that is harmless to the human body, and it can actually be used by putting it in a diaper. Publicly known literature Patent documents
[0014] [Patent Document 1] Patent No. 351334 Mitsubishi Electric [Patent Document 2] Patent Application No. 2003-160312 Mitsubishi Electric [Patent Document 3] Patent No. 3641608 Toshiba, Mitsubishi Electric [Patent Document 4] Patent No. 3900662 Ishikawajima-Harima [Patent Document 5] Patent No. 3278663 Sumitomo Precision Products [Patent Document 6] Patent No. 3513134 Mitsubishi Electric Summary of the Invention [Problem to be solved by the invention]
[0015] Plating quartz pipes SiO2 is very difficult with normal chemical plating. For this reason, AIP and CVD are used in a vacuum chamber where high voltage is applied between targets (+) and (-), and the target instantly reaches its boiling point with electrical energy and adheres to the coating object (-) as evaporated metal ions. This is AIP (arc ion plating method), and like CVD, the temperature is high at MAX 1000°C ± 100°C because the adhesion is achieved by the separation action of gas (CO2, N2) molecules. On the other hand, AIP is a medium temperature at MAX 600°C. Metals such as W and Mo are fired simultaneously at this AIP target, and two types of materials, such as Cr+W, Ti+W, Cr+Mo, and Ti+Mo, are simultaneously coated on the outside and part of the inside of the base quartz pipe. The present invention To provide a method for manufacturing an ozone generator which generates low-concentration ozone and has excellent utility effects such as indoor health environment management by mixing ozone. [Means for solving the problem]
[0016] The main characteristic technology of the present invention that satisfies the above-mentioned problems is as follows (1). (1) An ozone generator that generates ozone gas by supplying a high-frequency current from a high-frequency power source (21) to a quartz pipe (202) of a quartz pipe-type discharge tube (200) and supplying air from an air pump (22), The outer surface of the quartz pipe (202) of the quartz pipe type discharge tube (200) is previously coated with two kinds of metals, W, Mo, Zr, or Nb, and Ti, Cr, or Ni, by vapor deposition. Further, the inner surface of the quartz tube (202) is coated with powder flux of boric acid and copper chloride by fusion baking, an ejector (203) is connected to the air inlet side of the quartz pipe (202) which has been subjected to the deposition coating and the fusion baking coating, and a magnet chamber (205) in which a neodymium magnet (204) is disposed is connected to the outlet side of the quartz pipe (202)
[0017] That is, the present invention Low-concentration ozone is generated using inexpensive materials to reduce indoor ozone levels.The present invention provides excellent effects in terms of utilization, such as the realization of indoor health environment management by mixing zoonoses. The present invention will be described in detail in the "Effects of the Invention" section below. [Brief description of the drawings]
[0018] [Figure 1] FIG. 1 is a schematic explanatory diagram showing an embodiment of an AIP device of the present invention. [Diagram 2] 1A and 1B are explanatory longitudinal sectional views (1) and (3) of two targets in an AIP device of the present invention, and explanatory plan views (2) and (4). [Diagram 3] FIG. 3 is a longitudinal cross-sectional explanatory diagram showing a model of a quartz pipe-type discharge tube to be attached to an ozone generator, in which evaporated and ionized metal is deposited on the SiO2 pipe used as the base material 114 of the AIP device in FIGS. 1 and 2. [Figure 4] FIG. 4 is a simplified overall explanatory diagram of the world's smallest small-sized ozone generator equipped with the quartz pipe-type discharge tube shown in FIG. 3. [Diagram 5] FIG. 2 is an explanatory diagram showing the fusion baking coating process (enamel baking coating) on the inner wall surface of a quartz pipe. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] Next, an embodiment of the present invention will be described in detail with reference to FIGS. As shown in Figure 1 For the present invention The AIP device is used for suction purging of inert gases N2 and CO2, and for N2 and CO2 gas of In a vacuum chamber 100 that allows for evacuation, two disk-shaped targets 103 and 104 serving as arc power sources 101 and 102 and a coating material serving as a bias power source 105 are placed. (Base material: This example is quartz (SiO 2 ) Pipe-type discharge tube) A turntable 106 for placing the above-mentioned is provided. In FIG. 2(1) to (4), the one target 103 is a cylindrical target placed between a W or Mo electrode 108 or 112 on a Cu piece 107 having good electrical conductivity. Cr109 or 113 as evaporation metal As shown in FIG. 2 (2) and (4), these are embedded at predetermined intervals in the circumferential direction.
[0020] Similarly, the other target 104 is a cylindrical target between a W or Mo electrode 112 and a Cu piece 110 having good electrical conductivity. Ti as evaporation metal 113 are provided, and these are embedded at predetermined intervals in the circumferential direction. The two targets 103 and 104 are simultaneously subjected to arc discharge to produce W or Mo and Each for evaporation metal Cr 109, Ti 113 is evaporated and projected onto the base material 114 (the object to be coated) on the table 106, and W or Mo and the above are applied to the base material 114. Each for evaporation metal Cr 109, Ti 113 to thin film Evaporation To do so.
[0021] The AIP targets are close to pure metals, generally Cr, Ti, and Zr, and because they are made by powder sintering, they also contain trace elements such as V, Ta, and Nb, but targets with extremely different melting points are special products, and even the smallest unit of two targets costs several hundred thousand yen. As an example, if a 10 mm diameter W target is placed in a Cr target, a thin film with W particles in Cr can be created, although the area ratio is 6.2%. This is because the center of the target generates heat well due to its electrical properties, as shown in the AIP device in Figure 1. The boiling point of W is 5555°C, while that of Cr is 2672°C, which is more than twice as high. By pressing it into the phosphate bronze (Cu-P) at the bottom, the electrical conductivity is improved, and by applying more than twice the current to the target, it melts even though it has a high boiling point.
[0022] (2) Target The main metal 113 which becomes 103 and 104 and the evaporated metal 109 The physical constants are shown in Table 1. That is, the surface is treated with AIP to improve hardness. As described in Table 1 Metal is the main component. As shown in Table 1 Main Metal 113 : Cr, Ti, Ni metal deposition 109 : It is possible to add W, Mo, Zr, and Nb. Use as an AIP target mainMetals: As the physical constant of 113 indicates, they have high electrical resistance, high melting points, and proportionally high boiling points. Metals that are easy to nitride by creating a vacuum and using molecular gases such as N2 or CO2 as the replacement gas, and metals that are easy to create carbides by adding carbon, are the main types, and the purpose of more than 90% is to increase the wear resistance effect by using a hardened layer. As is clear from Table 1, the targets 103 and 104 are made of a base material: quartz (SiO 2) It goes without saying that it is possible to vapor-deposit coating the outer surface of the pipe 114 with two kinds of metals, one of W, Mo, Zr, or Nb and the other of Ti, Cr, or Ni.
[0023] [Table 1] TIFF2025068883000017.tif26170 <Example when base material 114 is a quartz pipe> The quartz pipe improves the electrical conductivity of the ozone generator by depositing metal ions on the outer surface and both end faces. SiO2 is close to an insulator with a dielectric constant of 1MHZ: 3.7~3.9 SiO2 Breakdown Voltage KV / mm 25~40 Volume resistivity of SiO2 Ωcm 1016 Dielectric constant of ceramic Al2O3 1MHZ: 9.5~10 Dielectric breakdown voltage of ceramics KV / mm 10~14 Volume resistivity of ceramics Ωcm 1014 The poor electrical conductivity of 100% Al2O3 is the main cause of the air breakdown, which acts like an electric capacitor, resulting in the formation of O2 → O + O → O + O2 → O3. 10-6 2cm, W=13 10-6 Although the electrical conductivity of SiO2 and Al2O3 is so poor that it is not an issue, plating SiO2 to allow a continuous current to flow is extremely difficult, but the inventor has succeeded in doing so separately.
[0024] (3) In the AIP method, the inside surface of the quartz pipe is coated by a few percent, so even if the quartz pipe of the ozone generator tube is 15 mm in outer diameter, 13 mm in inner diameter, and 50 mm in length, only up to 5 mm at both ends is coated, and it is impossible to coat the inside of the quartz pipe. Conventionally, air is an insulator, so ozone O3 is generated by increasing the high-frequency voltage and applying a high voltage to O2, and the process O+O→O+O2 is generated. However, if the inside of the quartz pipe is a conductor, continuous coastal discharge is possible with a low voltage. The outside is ionized by AIP. Possible By depositing a metal coating and baking a thin metal coating (Cu+P) on the inside, electrical conductivity is improved and O3 can be generated at a low voltage. TIFF2025068883000018.tif11150 Inside the pipe hole for electroplating: Inside Coating is possible up to a range of 2 to 3 mm on both ends of the edge. This teeth This is demonstrated by the model shown in Fig. 4. In other words, in the discharge tube 200 made of a quartz pipe (outer diameter 15 mm x inner diameter 13 mm x length 38 mm) which is an example of the base material 114, a spring 201 made of phosphorus copper plate with a thickness of 0.1 mm (Cu-P) is attached to the inner surface of the quartz pipe 202 by its spring force to continuously generate a bath-bank discharge, thereby extending the life of the high frequency power source. O3 is generated at 70% of the capacity of the design value. Cu-P has such a strong spring force that it is also called Cu spring steel, and therefore adheres 100% to the inner surface of the quartz pipe 202, allowing electricity to flow stably.
[0025] (4) The inlet of the discharge tube 200 is heated by the ejector 203 method, which increases the inlet air by about 30% and increases the amount of O3 generated. The decomposition of O3 is slowed down by passing it through a neodymium magnet 204 with a total of 9000 to 9800 G at the outlet. The half-life of O3 is 16 hours, but it is strongly retained because it is a dilute ozone O3 at 0.01 to 0.02 PPM / h. The air inside the quartz pipe 202 is instantly destroyed by high temperature and pressure, electricity is passed through it, and O3 is produced. However, in the conventional single pipe system, the pressure of the air that is instantly destroyed and expanded increases by 30% or more, so the air intake side uses an ejector 203 system that can withstand the 30% expansion pressure and cover the amount of air that is needed. In addition, since the expansion pressure leads to an increase in speed, a magnetic field chamber 205 containing neodymium magnets 204 that receive the primary air is installed on the outlet side to suppress the decomposition of O3. The entire magnetic field chamber 205 is within the magnetic field lines of a 9000 gauss neodymium magnet, and since the half-life of O3 is short at 16 hours, the Japanese safety standard is for the atmospheric concentration to be within 0.01 to 0.05 ppm, with 3 to 5 minutes of operation and 15 to 20 minutes of rest, so the electromagnetic release is used to slow down the decomposition of weak ozone O3.
[0026] (5) The SiO2 of the quartz pipe 202 is not 100% deposited. Moreover, no expensive reducing agent such as Pd is required. Boric acid (180-800℃) and copper chloride (650℃) are mixed in a 50:50 ratio for each powder, and held at a maximum of 700℃ for 30 minutes to enable thermal plating. The material is not even a flux, but a simple mixture of the two types of materials, and the quartz pipe is melted and baked on this flux using a convection method. This method is not a stable thermal deposition plating because SiO2+H3BO3+CuCl2 is attached, and there is variation, but for the first time, baking plating is possible without using expensive AIP or CVD. The procedure was a plating method, which will be described later, and only the final process involved baking at 850°C. CuBF4 (copper borofluoride) is used around 800℃. The halogens F, CL, and Br are necessary for etching the quartz pipe 202. Boric acid and CuCl2 (copper chloride), H3BO3 (boric acid) and CuBF4 (copper borofluoride) are up to a maximum of 800℃. I am certain that 100% plating cannot be achieved on the quartz pipe 202 of the ozone generating discharge tube by normal methods. Even the etching method (halogen-HF) is impossible with SiO2. That is why I resorted to the AIP method. Another method is enamel, which isBaked at 700 to 800°C. If the material is viscous like enamel, it is impossible to use the spring force to make the Cu-P foil adhere to the inner surface of the quartz pipe 202. The flux must be liquid, and even after 10 coats and baking, the resulting film is 1 μm to 2 μm thick. It is important that the flux is 100% liquid. This is possible because the inventor has the technology to make brazing flux in liquid form as shown in the liquid flux of Patent No. 4736105, but it was extremely difficult to do with SiO2. In a heating furnace, H3BO3 (boric acid: 180-800℃) will evaporate as a single substance, so CuCl2 (copper chloride, 650℃) is added to make it liquid, and these two are placed in a separate container and the evaporation and ionization by themselves makes it possible to plate, but it takes a long time at 850℃, so productivity is lacking.
[0027] (6) The inventor has taken on many challenges with quartz (SiO2) over the last three years, but fusion was not possible unless heat of 500-800°C was applied. Metal ions (Xn, Cu, Ni, Sn, Sb, Cr, Fe) were added to 100% halogen flux, and experiments were conducted up to cyanide (Nc) for stability, but 100% plating was impossible after several hundred experiments. The baking flux (one type of enamel) is 100% enamel-like. Since SiO2 can withstand up to 1800°C, it is a flux close to a glass-like glaze. Since SiO2 can withstand up to 1800°C, expensive AIP and CVD processing are not necessary if glaze is made at 600-800°C. It cannot be called a soldering flux, but is more like enamel. The inventor has been developing fluxes for 42 years, mainly for brazing, at a welding rod manufacturer, and thought that he could tackle SiO2 with relatively little resistance. He thought of it as just an extension of the flux used for brazing ceramics, but it took him three years. The biggest reason was that he had decided not to use white group elements such as Pd, Ir, Pt, and Ru, which act as inorganic reduction catalysts. PdCl2 is also used for glass plating. He does not use anything more expensive than gold. Cost-wise, it is possible to make 1g for more than 30,000 yen because it is an automobile catalyst, but such an expensive metal cannot be used in a device that costs several tens of thousands of yen. As mentioned above (0025) was successful, the composition is shown, but since it is 100% liquid, it takes about 10 bakings to make it 1μm to 2μm thick. For an ozone generator for SiO2, this level of liquid Copper soldering is also possible with flux.
[0028] (7) It became possible to plate the quartz pipe 202 using the liquid flux baking method (MAX 850℃), but the thickness was only 1μm after five bakings. It has been found that plating the quartz pipe 202 is almost 100% impossible to do using any method other than CVD and AIP. In the experiment What was discovered was that the coating was baked on by heating (700-800℃). The liquid flux made in the final process described above is baked at 850℃ with a maximum of 130cc per time, and gradually condenses in the air in a small bottle. The bottle is 15mm in diameter, 13mm in diameter, and 50mm long, so it is baked in the air at 850℃ and then quenched in the bottle. liquid The flux is baked (100℃). It gradually thickens and becomes 1μm thick after 5 to 6 baking processes. Because the items are small, we don't make them in large quantities. It is not like chemical plating because each reaction is random. This is handmade baking plating. Similar to enamel, it is baked with a gas burner at 800-850℃. It would be ideal if it could be done 360° all at once like high frequency, but we lack the funds. If Ar gas is injected and sealed in every time the final liquid flux is applied and the temperature is increased to 850℃, it will not become copper oxide, so a perfect discharge tube for O3 generation can be made.
[0029] (8) Ohm's Law: E(voltage) = I(current) x R(resistance). B. 0.01~0.05mg / h: Harmless to the human body; 100% for diapers B. 10-30mg / h: In a large room with only 1-2 diaper-wearing patients in the room, the odor is strong, so the concentration is operated for 2-3 minutes and then the room is rested for 30 minutes. Capacity of the large room is 10m x 5m x 8m = 400m 3 ÷2.14=186.9mg / h, 186.9mg / h÷3 / 60=9.345mg / h÷30=0.31mg / h Ha, diaper collection room in the hospital (room for storing diapers for 10 to 14 days): 5m x 5m x 5m = 125m 3 , 500mg to 600mg / h 125m 3 ÷2.14=58.4mg / h 60 minutes - 3 minutes - 60 minutes - 3 minutes drive 58.4÷3=19.47mg÷60=0.32mg / h This is how you control the O3 with just one unit. Therefore, in numerous experiments, the current was controlled very precisely to 0.01 to 0.18 Ampere. R=950~980V. 2. People who wear diapers for 4-5 people with a care level of 4-5 suffer from a complex odor from the other 4-5 people, including their own. If this odor is eliminated with ozone O3, the unique odor of the hospital room returns. By simultaneously spraying the forest scent with relaxing essential oils, we can provide an aromatherapy bath for sick people who cannot move. This oil is a low-cost oil made by recovering essential oils from the exhaust steam of wood drying. The suffering of patients with a care level of 4-5 who wear diapers around the clock is caused by the combined odors of the other 4-5 people, including their own. Eliminating this odor with ozone restores the clean odor that is unique to hospital rooms. In addition, spraying relaxing essential oil with a soothing forest scent provides an aromatherapy bath for patients who cannot move. We recommend using low-cost essential oils recovered from wood dryers.
[0030] (9) Although the O3 concentration is extremely high at 500-600 mg / h, there are many places suitable for high concentrations as long as the timer setting is not mistaken. For example, the smell of cutting oil in machining is eliminated, and 0.015-0.018 mg / h of ozone discharged into the factory completely eliminates the smell in the machine room. Effects of the invention
[0031] The ozone generator equipped with the quartz pipe in the present invention is a small air-cooled type. Moreover, although it is small, it needs to be operated continuously for a long period of time (5 to 6 years) and therefore needs to be made into a discharge tube with humidity countermeasures (Japan has a rainy season), and it is safe to say that plating quartz pipes (SiO2) is impossible. The inventor worked for a welding rod manufacturer for 42 years, developing various flux gases and metal welding as well as plating solutions and solvents for quartz (SiO2) in the solder flux and dissimilar material joining technology development department, but he thought plating was impossible, so he also developed something that was in a glaze state similar to enamel. As a result of experiments at 50 degree differences from 450 to 850°C, it was possible to apply copper glaze to SiO2 by baking boric acid (H3BO3) alone and copper ions Cu(BF4)2, CuCl2, CuCO3, etc. at 650 to 850°C.
[0032] In the enamel firing method, the discharge tube is small, 15mm outer diameter x 13mm inner diameter x 50mm length, so the dot attachment part of the holder is a capillary tube, and the holder becomes a real dot and is attached thickly. Since a thin plate of Cu+P is inserted on the inside, the inside cannot be held, and the jig that holds it upright in the furnace can only be used once, which is time-consuming. For this reason, both AIP-Ti+W and Cr+W were made, but the specific electrical resistance of Ti was -4.2×10 -6 Ωcm, W is 12.4×10 -6 Ωcm, Specific electrical resistivity of Cr - 13 x 10 -6 Ωcm It is possible to embed 6.3% W in the main Cr target and simultaneously use the heating pole target because W is a member of the Cr group. Two types of ions are fired at the same time to coat the material. Thermal conductivity (Cal cm -3 .scc -1 (C), Cr=0.16 W=0.13, similar to the previous example, but the boiling points are high, Cr=2500℃ and W=5555℃. IonizableThe particles are 3 to 10 times larger than Cr, which creates irregularities on the outer surface (15 mm). Only W appears convex. (This is because a high melting point metal is embedded between the AIP electrodes to create a target.)
[0033] As mentioned above, lightning strikes high places. The convex particles act as lightning rods. Since there is a convex part with an outer diameter of 15 mm and an outer circumference area ratio of 6.3%, by wrapping it twice or three times with 800 to 1000 mesh copper wire mesh, Because of the point contact, lightning strikes the 6.3% lightning rod continuously. The inside diameter of the pipe is made of a Cu+P 0.1% cylinder with a thickness of 412.7-12.8 mm, so the pipe is insulated with a (+) front and back relationship. The insulation of the SiO2 quartz pipe can be easily broken, allowing high-voltage corona discharge. The gap between the (-) pole is 0.4 mm, which is neither a spark discharge nor a glow discharge; it is more like a corona discharge and no sparks are visible. In air, it is an insulator, and only when exposed to high voltage electricity does O2 decompose to become O+O, and does not decompose. O2+O→O3 is produced. Air is 21% O2 and 78% N2 gas. N2→N+N decomposes. During the rainy season, humidity is high, so H2O→H+H+O+N+N becomes (OH)NX(O3). NH3 (ammonia) and other compounds must have been produced. Because of this, the Earth's magnetic field protects ozone from three types of ultraviolet light: UVA, UVB, and UVC, which is why humans came onto land about 3.5 billion years ago and it took 3.5 billion years for us humans to be born. In order to protect O3, in the next process, O3 passes through a 9000G magnetic field to minimize ultraviolet light.
[0034] Largest room: 5m x 5m x 8m = 200m 3 Assuming that there are seven people wearing diapers in the room, how much ozone should be sprayed into the room? If we calculate using 500mg / h and 1000mg / h, the result is: 1) 500÷200÷2.14=1.168ppm If the average distance to the diaper is 5m per person, then 1.168÷5=0.2336ppm In reality, the hose is 46 x 5 mm and has an inner diameter of 4 mm.) It decays as the square of the total length of the hose. 1.168÷25=0.047ppm 2), 1000÷200÷2.14=1.168ppm÷25=0.0935ppm→about 0.1, so spraying for 5 minutes and then resting for 15 minutes will break down O3 sufficiently. 0.1×0.25 / 16=0.0016ppm After 15 minutes, the half-life of O3 in the ultra-safe zone is 16 hours, so even with a time difference (continuous operation with a timer set) of 500mg~1000mg / h, the diaper odor in the patient room will be absorbed.
[0035] Up to eight people are allowed, but the limit is seven because when washing the buttocks with one spray pipe, ozone gas gets mixed into the mist of water for cleaning, and hydroradicals (OH) are generated overnight. - This is because it reacts more strongly with water (humidity) than O3. The traditional method of wiping with water is not 100% disinfectant, and since the urethra and anus are close to each other, people who wear diapers can get a disease called "cystitis" when bacteria multiply in the bladder due to germs passing through the urethra, causing inflammation of the bladder mucosa. Women's urethras are short, so bacteria can easily reach the bladder. Those with a care level of 4 to 5 have a difficult disease. Nurses are also relieved from the smell. There is no rash on the patient's bottom, and good cleanliness is maintained. Currently, inpatient caregivers have to change diapers 4-5 times per day. 7 people x 5 times x 10 hospital rooms = 45 times, which means battling odors and uncleanliness. I am deeply humbled by the caregivers. My late wife was cared for by this for a year and a half. This is what led to this invention. People who can die 100% diaper-free are truly lucky. 100% of humans will eventually die. Imagine yourself in a hospital bed wearing a diaper. Is there any privacy for your bottom? Changing diapers without an odor is beneficial not only for caregivers, nurses entering the patient's room, but also for visitors as there is no odor emanating from diapers in the room.
[0036] The cause of cystitis is bacteria that reach the bladder by taking advantage of the weakened immune system of hospitalized patients, but compared to men, women have a shorter urethra due to differences in their physical structure. For women who wear diapers, the water on the spray bottle mixes with O3 to keep the buttocks moist after changing the diaper. Conventionally, it was a water-washed wipe, but it was impossible to remove germs. Women are more prone to urinary tract diseases than men because of menstruation, pregnancy, childbirth, menopause, etc. They are prone to cystitis, which causes frequent urination, urinary leakage, itching, fever, and blood in the urine. Nowadays, there are antibiotics, so symptoms improve in 3 to 4 days, but there is little urine output, and bacteria easily grow in the bladder. Those with nursing level 4 to 5 are unable to move or talk on their own, and are kept alive. They are not human, but are close to a vegetative state. Families and visitors hesitate to take their feet because of the smell in the hospital room. When a patient becomes a vegetative state, the hospital will not 100% determine that they have cystitis until they have blood in their urine. Infection can even occur up to the kidneys, and the sprayed ozone of this invention has a strong bactericidal effect that is 2 to 3 times stronger than the hydroradical (OH)O3.
[0037] Bacteria in feces (80% of which are E. coli) that adhere to a woman's genitals can invade the bladder through the urethra and grow, causing cystitis. The female urethra is 3-4cm long, while the male urethra is 20-25cm long, and although fecal bacteria are invisible to the naked eye, they adhere 100% to the pubic hair and vaginal area. Ozone O3 continues to kill these bacteria even while the diaper is in place, making it difficult for the condition to develop into cystitis. Menstruating women can get cystitis if they wear a wet pad for a long time. The idea behind the diaper of this invention is to restore humanity as a human being. It also relieves the caregiver from odor, and is clean for washing the private parts, preventing cystitis.
[0038] Those with a nursing level of 4 to 5 are unable to urinate or defecate naturally, so they use diapers to take care of them. Urine passes directly through the urethra to the bladder through a vinyl pipe that is changed every day, and the daily urine volume is measured with a change once every 24 hours. It is mainly excreted from the kidneys. When kidney function is low or high, it is suspected to be a disease, and functional disorders such as chronic kidney disease (CKD) are judged to be serious diseases such as myocardial infarction, stroke, and end-stage renal failure. Therefore, the hose must be replaced every day. Because women have a short urethra, it is easy for germs to enter and they are prone to developing cystitis. If 0.02-0.03 ppm ozone is injected into the anus for 24 hours, germs around the urethra will be killed, making it safe. Creatine levels are proportional to muscle mass. For bedridden patients with a nursing level of 4-5, the amount of high protein they can get from their diet is a good indicator. For patients who are gradually becoming thinner, creatine is proof that they are alive. Men should be careful if their creatine levels exceed 1.2, and women should be careful if their creatine levels exceed 1.0. TIFF2025068883000019.tif9149Keeping it clean at all times also protects the kidneys. Ozone O3 injection (0.01-0.03ppm) is injected for 5 minutes, followed by a 15 minute break, and then operated continuously for 24 hours to keep it deodorized and clean. The inventor conducted numerous experiments while caring for his late wife while she was alive, and obtained patents No. 6,596,620 and No. 6,674,670 with the sole desire to enable his wife to live a humane life in hospital. The smell of one's own diapers is tolerable to a certain extent, but the combined smell of many other people's diapers in the room is strong, strange, and extremely difficult to bear. Despite this, I am humbled and grateful for the efforts made by nurses when changing diapers. One way to alleviate the burden of these people's efforts is to eliminate the smell in the diaper and to free patients from the smell of diapers. By spraying cypress oil, cedar oil, etc. along with ozone gas (0.01-0.05 ppm / h) as a form of "forest bathing," it is possible to completely free a hospital room from the smell of diapers. When changing diapers, wiping the bottom with a towel after the diaper change with wood acetic acid (a mixture of various essential oils) and cleaning the bottom also has a sterilizing effect of wood acetic acid, which helps maintain health.
[0039] AIP vacuum hardening film mainly creates a hardened layer, and the coating and target used up until now have been TiN, TiAlN, TiCN, CrN, and ZrCrN, mainly using ion particles in N2 gas. In a 100% Cr target, 6.3% of W ions in area ratio are simultaneously ionized into two types of targets, Cr about 94% and W about 6%, and deposited on a quartz pipe. Experiments were conducted on these two new targets 103 and 104 shown in (1) to (4) in Figure 2. Figure 2 (5) shows a target that has become uneven due to arc discharge. Due to arc discharge, the arc spot has a diameter of about 10 μm. 6 ~10 8 A / cm 2 The high density current, reaching up to 10000K, is concentrated, generating high temperatures of 4000-10000K as Joule heat, instantly melting and evaporating the cathode material, and evaporating refractory metals such as W (tungsten: 5555°C) and Mo (molybdenum: 4639°C) relatively easily. This time, the uneven particle ions of Cr+W are used as an interesting corona discharge, and although it has not been experimentally confirmed whether the bactericidal effect of W particles is as antibacterial as silver, copper, zinc, cobalt, and nickel, when humidity is added to the metal ions, the ion difference produces a bactericidal effect. The literature states that Cr, Mo, and Zn have antibacterial properties, so it is thought that W is due to being a Cr-based material.
[0040] There are four types of discharge: corona discharge, glow discharge, spark discharge, and arc discharge. Ozone is also produced by corona discharge and glow discharge. When the potential difference between the electrodes is increased, the air between the electrodes breaks down and an electric current flows, which reacts with the 21% oxygen in the air in the following order: O2 → O+O → O+O2 → O3, producing O3 gas. The melting points of Cr and W are close to 1:2, and the number of ions with a potential difference of about 6% between the two is delayed by about 6% in the time it takes for coastal discharge to occur in a 0.1mm thick x 35mm long pipe of Cu-P attached to the center. The uneven ionization current makes the corona discharge random, so the strength of the discharge improves the ozonization power. In addition, a magnetic field of 900G is passed through the ozone layer to protect it from proton ions blown from the sun, creating unprecedented ozone.
[0041] O3 is generated by uneven ion current, but conventionally, ozone is generated by pipes that enter through a hole of the same diameter and exit through the same hole. Air expansion due to high heat only increases the flow rate, but this does not produce as much O3. Therefore, to cover the air that expands by nearly 30%, the Venturi tube type Ejector 201 supplies air and maintains a constant flow, improving the conventional maximum by 30%. Because quartz glass is used as an air-cooled O3 generator, 100% metal ion coverage is impossible with AIP, and because CVD has a hard protective film, it can withstand rapid heating and cooling, but since no experiments have been conducted, the amount of ozone generated is unknown.
[0042] The liquid flux for baking, which took three years to develop, ,Figure 5 The fusion-baked coating process (also called enamel-baked coating) shown in Figure 1 has been successful to date.
[0043] The ingredients and composition of the etching solution in step 8 in Figure 5 are 1) Ammonium chloride NHCl: 75g / 200cc alcohol 2) Ammonium fluoride NH4F.HF: 20g / 200cc alcohol 3) Methanol CH3OH: 140cc 4) Ti etching solution HCl (50cc) + NH4F.HF (20g) + water (100cc) (Etching solution introduced in Patent No. 7108984) Also, in step 10, 4-2C-3A, the components and composition of the liquid flux introduced in Patent No. 4736105 are 1) Potassium fluoride KHF4: 50g / CH3OH 200cc 2) Potassium borofluoride KBF4: 50g / CH3OH 200cc 3) Potassium fluoride KF: 30g / CH3OH 200cc 4), Boric acid H2BO3: 50g / CH3OH 200cc 5) Methanol CH3OH: 200cc Also, the ingredients and composition of DMAB-2 (substitute for PdCl) in step 11 are 1) Diethyl sulfate (C2H5O)2SO4: 60cc 2) Hydrazine hydrate (NH2NH2·H2O): 50cc 3), 1-1'-1''-nitrilotri-2-propanol [(CH3.CH(OH)CH)]2N: 5g 4) Trimethylborane (70%)-(C8H8O3)B: 80cc Furthermore, the ingredients and composition of the ignition liquid in step 12 are 1), Copper borofluoride (45%) Cu(BF4)2:20cc 2) Diethylaminoborane (70%) (C3H8O4) B: 10cc 3) Potassium acid fluoride KHF4: 1g 4) Potassium borofluoride KBF4: 1g 5) Methanol (CH3OH): 100cc The above is the procedure for steps No. 1 to No. 12. It is impossible to do this with normal plating of quartz pipes. We tested enamel glaze just to be sure, but it was not possible to apply it evenly to a quartz pipe with an outer diameter of 15 mm, an inner diameter of 13 mm, and a length of 50 cm. Since we also had a patented technology called liquid flux, we baked everything in liquid form, so we ignited it 5 to 6 times with burner heating at 800℃ to 850℃. After 5 bakings, the inner and outer surfaces of the quartz pipe were plated with a thickness of 1μm.
[0044] The AIP method is mainly aimed at wear resistance, so the specific electrical resistivity of the metal is 10 -8 Ω.cm * Cr (chromium): 13 (28°C) * Fe (iron): 8.71 (0°C) * Sn (tin): 118.1 (0℃) * W (tungsten): 12.4 (0℃) * Ti (titanium): 4.2 (0℃) * Ag (silver): 1.50 (0℃) * Cu (copper): 1.55 (0℃) * Au (gold): 2.04 (0℃) * Mn (manganese): 185 (20℃) * Al (aluminum): 2.50 (0℃) In the AIP method, electricity does not flow easily through Cr, Ti, Zr, and W. Cu (copper) is the second most conductive material after silver. The chemical plating method is an alloy of Cu+α(B) and flows 8 times more. Quartz is said to be 100% impossible, but it is now possible to plate the inside and outside surfaces with Cr of about 1μm.
[0045] The inventor had conducted numerous experimental tests on his patent no. 611385, which involved plating on ordinary glass, so he thought it would be possible to use quartz as well. He had also been successful in using brazing flux on glass and dissimilar metals, so he thought he had the foundations, but he did not expect the oxide film of SiO2 to be so strong. There was no anchoring effect created by artificially roughening the surface with glass beads. It was entirely chemical etching. The reagents were mainly those containing fluorine. HF etching was also experimented with, but the results were lacking, and chemical plating was successful when baked.
[0046] The discharge tube shown in Figure 4 is made of a quartz pipe, with a thin aluminum adhesive wrapped around the outside to a thickness of about 1 mm. The inside is not covered with anything. The outside of the quartz pipe is (+) and the (-) pole blows out air under a gap of 0.3mm to 0.6mm inside, and since a high-frequency voltage (400 to 800V) is applied between 0.3 to 0.6mm, air electricity does not flow easily. The insulators discharge and explode, and it is called coastal discharge because it resembles the waves that reliably reach the shore 16 to 18 times per minute, which is generally called coastal discharge. O3 is produced when oxygen molecules are exposed to the sun's ultraviolet rays (UVA, UVB, UVC). TIFF2025068883000020.tif8149. Oxygen atoms (O) are born in lightning, and ozone O3 is also born. Lightning is a pathway in which static electricity particles in a cumulonimbus cloud instantly discharge between the ground and the cloud, in a so-called plasma state where electrons and positive ions coexist, and travels in a random direction with the electrons and positive ions. Oxygen molecules in the air are struck by the high-speed electrons, some of which become oxygen atoms and combine with the oxygen molecules to create ozone. Since this phenomenon occurs inside the quartz pipe, which is the discharge tube, the quartz pipe needs to be copper plated to allow electricity to flow easily.
[0047] If we imagine the Earth as an ozone discharge tube, the iron-nickel alloy at the core of the Earth creates a magnetic field as the Earth rotates. Without this magnetic field, the solar wind would pour intense ultraviolet rays (UVC, UVB) onto the Earth. 3.5 billion years ago, animals emerged from the sea onto land because plants in the sea produced O2 and created the ozone layer, allowing them to survive. The North and South Poles are places where magnetic field lines are concentrated, and most of the solar wind flows along the Earth's magnetic field, but some of it becomes an excited ionized state with O2, N2, O, and N molecules as the aurora, and high-energy atoms enter the orbital electrons that atoms normally have, causing them to become excited and emit electromagnetic waves, resulting in the complex atomic colors of the aurora, red, white, purple, green, and blue. I imagine that the inside of the discharge tube is also in a similar state. O3 is born from the air in this way. O3 is too strong in diapers as it is, so a magnetic field charging method is used.
[0048] The ozone concentration at which ozone affects life in nature occurs at 0.02 to 0.03 ppm. Some of it falls by convection from the ozone layer, reaching harmful concentrations near the poles. In urban areas, photochemical smog is generated by automobile exhaust and factory exhaust, the main component of which is ozone. Human activities produce ozone, which does not exist in nature, and this has a compounding effect that damages human DNA even with ultraviolet rays (UVA) and even the weakest ultraviolet rays. Large diapers are necessary for sewers, swimming pools (urine treatment plants, wastewater treatment plants, semiconductor etching, pulp bleaching, food sterilization, aquarium water purification, tap water odor removal, etc., but there are almost no measures to prevent odor and sterilization for hospitalized patients. On the contrary, diapers with urine absorption resin are becoming the mainstream. They absorb urine and swell thickly, and the genitals and surrounding area become warm with nearly 100% humidity and 35-36℃, which leads to the proliferation of germs (E. coli). In this situation, the Ministry of Health, Labor and Welfare is recommending the use of urine absorption diapers as a measure to deal with labor shortages, but this leads to an increase in medical expenses. Even with cheap diapers, the injection of diluted ozone gas that does not remain in the environment eliminates indoor humidity, bad odors, and germs, maintaining comfort and realizing a comfortable hospital room.
[0049] Humans have the wisdom to use and develop tools, but they exploit the earth's resources, and their activity has led to global warming and the destruction of the ozone layer, and they are constantly destroying the environment in pursuit of profit. If we continue like this, it is said that the temperature will rise by 4.3 degrees Celsius by 2100. Meanwhile, 80% of Japan's electricity is generated by thermal power plants, which produce large amounts of CO2 with no end in sight. On the other hand, 80% of nuclear power plants are not operating, so it is very questionable how they can reduce CO2 concentrations. In the present era, we have been fortunate enough to limit the rise in temperature to 1.4 degrees Celsius, but with rising sea levels, desertification, forest fires, and the massive production of methane gas (which has four times the global warming effect of CO2 production) due to the melting of permafrost in Russia, the Earth is no longer just warming, but is on the brink of a boiling point. In this critical situation, bedridden patients with a nursing level of 4 to 5 are the ones who are not being taken into consideration when it comes to diaper measures. Even healthy people, including medical personnel, do not know when they will need diapers, so we should keep in mind that we are now in an era when diaper measures using ozone according to the present invention should be adopted as soon as possible.
[0050] The way ozone gas is made is to make the inside and outside surfaces of the quartz pipe more conductive by plating with Cu ions, then to make the outside of the quartz pipe the (+) electrode, create a thundercloud (cumulonimbus cloud), wrap a 45mm wide 800 mesh wire net three times, and to break the air layer by applying a high-frequency high voltage to the quartz tube in the middle pipe and the Al electrode (-) + anodized, a discharge continuously generates O3 in a gap of 0.4 to 0.6 mm, and the process of O2 → O + O → O + O2 → O3 reacts instantly to generate ozone O3. In the natural world on earth, ozone is also produced by ultraviolet rays and lightning discharge, so we inhale or are exposed to 0.01 to 0.05 ppm of ozone, but it is not a scary gas. In the small gap of 0.4~0.6mm, the continuous discharge column converts O2 molecular gas into oxygen electrons of O, and by repeating recombination, O3 gas is released, which is just right for the human body. Now, if we calculate the size of the room as 5m x 5m x 2.4m = 60m3, 200mg / h÷60÷2.14×15 / 960min=0.024ppm. 15 minutes is roughly within the safety standard. Commercially available ozone (mainly made in China, such as on Amazon) is mostly 500mg / h to 1000mg / h. 500mg / h÷60÷2.14×3min / 960min=0.001ppm, so the timer will be set from 3 minutes (operating) to 5 minutes (resting).
[0051] If we consider the Earth to be a single living organism, the "Gaia hypothesis" is valid. It was insects that emerged from the sea onto land 420 million years ago, and vertebrates emerged on land about 100 million years ago. Ozone gas, which protects us from ultraviolet rays, was produced over the course of 320 million years from oxygen gas emanating from the sea. Plants reduce CO2 gas through photosynthesis and produce O2 gas, which has created the Earth we know today. It is believed that without the ozone layer, the Earth would not exist as it is today because DNA would not be protected from the strong ultraviolet rays (UVA, UVB, UVC) from the sun. Humans are also damaging this ozone layer. UVA (wavelength 100-280mm), UVB (wavelength 280-315mm), UVC (wavelength 315-400mm), visible light (wavelength 400mm-760mm), infrared rays (wavelength over 760mm). According to the "Gaia hypothesis," the ozone layer protects terrestrial organisms from harmful ultraviolet rays, and animals are born only when forests and grasslands, which can be considered the muscles and internal organs of the living Earth, begin to live. The ozone layer descends to the ground through the Earth's convection currents, so it is closely related to sterilization, organic matter decomposition, immune activation, and existing signals. Higher animals such as humans cannot survive without ozone. The Gaia hypothesis states that the Earth is alive because plants produce oxygen and ozone is produced from that oxygen.
[0052] 3 and 4 show a model of an ozone generator that is the basis of the quartz pipe discharge tube of the present invention. The entire core is made in Japan. The ozone generator generates ozone gas by supplying a high-frequency current from a high-frequency power source 21 to a quartz pipe type discharge tube 200 and also supplying air from an air pump 22. The quartz pipe type discharge tube 200 is a type in which Cu is baked and coated on a quartz pipe 202, Cu foil or a steel wall is wrapped around the outer tube, and a spring pipe 201 made of Cu+P is tightly attached to the inner wall of the quartz pipe 202, and a high current is continuously supplied from the high-frequency power source through the air pump 22 via the ejector 203 to increase the amount of air introduced and break the insulation. Also, as a measure against thermal expansion of the air, a magnet chamber 205 is provided on the outlet side of the quartz tube pipe 202, so that even if the magnet chamber 205 receives an increase in the speed of O3 generated due to thermal expansion, the O3 is magnetized within the magnet chamber 205, so that 0.02 to 0.03 ppm is maintained outside the hose with an outer diameter of 6 mm, inner diameter of 4 mm, and a maximum length of 10 m.
[0053] Healthy people are constantly experiencing stress outside of work. How happy would it be to take the time to relax on a day off and relax surrounded by the scents of forest bathing? The source of the forest scent is the essential oils contained in cedar, cypress, etc., which are distilled and are very expensive. Forest cedar, cypress, etc. are turned into building materials by force-drying the wood's own moisture content of 150% to 20%. The essential oils are extracted and collected by cooling the exhaust steam from the wood drying pots. This is steam that is originally released into the atmosphere. By installing a cooling device, it can be collected semi-permanently. Drying wood is used as a building material to prevent defects in the building structure due to deformation and shrinkage. The drying kiln is expected to operate indefinitely. Therefore, as long as the cooling system that was created once is operational, it is possible to recover the essential oils from wood at a low cost. Ozone eliminates all odors, including the patient's body odor and urine odor, leaving only the pleasant, distinctive smell of the hospital room. The constant supply of the forest scent helps patients relax and aids in their recovery. The sawmill produces 100% waste-free wood, as essential oils are extracted from the sawing, bark, and chips of cedar, cypress, and other trees and used to fuel boilers. [Industrial Applicability]
[0054] As described above, the present invention provides a number of useful effects, including the protection of many people with diseases requiring long-term care by using a small ozone supplying device for diapers, which is achieved by plating metal ions onto targets for evaporating and ionizing metals by arc discharge, quartz pipes for ozone generating discharge tubes, and wear-resistant metal machine parts, the management of indoor health environments by mixing ozone into humidifiers, and the securing of ultra-hardness by plating metal ions onto golf club heads, thereby ensuring dramatically long flight distances, and will greatly contribute to the plating industry and the ozone utilization industry. [Explanation of symbols]
[0055] 100: Vacuum chamber 101, 102: Arc power supply 103, 104: Target 105: Bias power supply 106: Turntable 107, 110: Cu peace seat 108, 112: W electrodes 109, 113: Vaporizable and ionizable metals 114: Base material (coated object: quartz pipe) 200: Quartz pipe discharge tube (outer diameter 15 mm x inner diameter 13 mm x length 38 mm) 201: Spring 202: Quartz pipe 203: Ejector 204: Neodymium magnet 205:Magnetic field chamber
Claims
【Request 1】 A quartz pipe coated with two different kinds of vaporized / ionized metals, Cr+W, Ti+W, Cr+Mo, Ti+Mo, or boric acid and copper chloride powders are mixed in a specific ratio to form a flux. The quartz pipe is placed on the flux by convection at a maximum temperature of 700℃ to melt and bake it. 2 +H 3 BO 3 +CuCl 2 1. A quartz pipe discharge tube for an ozone generator, comprising a quartz pipe having a chemical plating. 【Request 2】 The quartz pipe discharge tube has an ejector 203 type air intake side to increase the inlet air 3 The amount of generated air also increased, and 204 neodymium magnets with a total of 9000 to 9800 G were placed on the outlet side to receive the primary air. 3 2. The quartz pipe type discharge tube of the ozone generator according to claim 1, further comprising a magnetic field chamber 205 for slowing down the decomposition of
Citation Information
Patent Citations
Discharge tube for ozone generation
JP2009091209A
Discharge device and air cleaner
JP2017120697A
Ozone generator
JP2020066536A
Mask
JP2021165452A
Crystal oscillator
JP2004363980A